1970
DOI: 10.3329/bjb.v38i2.5150
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype of some species of <i>Chara</i> and <i>Nitella</i> (Charophyta) from Bangladesh

Abstract: Karyotypic analysis of Chara corallina Linn., C. vulgaris Linn., C. gymnopitys Linn. and Nitella translucens Ag. collected from natural habitats revealed that C. corallina has n=42, C. vulgaris and Chara gymnopitys have n=14 while Nitella translucens has n=18 chromosomes. All the species had differences in individual chromosome length, total chromatin length, total frequency between the complements of their chromosomes. Cytological investigation on the chromosome number in members of charophyta from India have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The karyotype within the genus Chara is considered to be symmetrical and the majority of taxa have a dominance of metacentric and sub-metacentric chromosomes (Singh and Chaudhary 2010;Khatun et al 2009). In present study, four Chara species showed high values of TF% (> 40) and contained a symmetrical karyotype.…”
Section: Longibracteatasupporting
confidence: 45%
See 1 more Smart Citation
“…The karyotype within the genus Chara is considered to be symmetrical and the majority of taxa have a dominance of metacentric and sub-metacentric chromosomes (Singh and Chaudhary 2010;Khatun et al 2009). In present study, four Chara species showed high values of TF% (> 40) and contained a symmetrical karyotype.…”
Section: Longibracteatasupporting
confidence: 45%
“…ANOVA and LSD tests revealed significant differences in the total size of chromosomes, size of the long arms, size of the short arms and the arm ratio among the populations of each species and varieties studied, 1967a, 1967bMirasidov 1971;Grant and Proctor 1972;Khatun et al 2009) reported the occurrence of n =14, 18, 28, and 42, but n = 14 and 28 are the most frequent chromosome counts for this species (Singh and Chaudhary 2010).…”
Section: Longibracteatamentioning
confidence: 99%